Upaya Meningkatkan Hasil Belajar IPA Materi Gerak Dan Gaya Melalui Metode Demonstrasi Pada Siswa Kelas VII G SMP Negeri 13 Kota Magelang Tahun Pelajaran 2022/2023 - Ngatini, Ngatini (Faculty Of Education, 2024)
This research aims to: 1) Describe the process of implementing the Demonstration Method in improving science learning outcomes on Movement and Force material for students in class VII G of SMP Negeri 13 Magelang City. 2) Describe the level of science learning outcomes on Movement and Force material in class VII G students of SMP Negeri 13 Magelang City after implementing the Demonstration Method. This research is classroom action research, which consists of two cycles, each cycle consisting of three stages of activities, namely; planning, action and observation, and reflection. The research subjects were 30 students in class VII G at SMP Negeri 13 Magelang. Data collection in this research used observation sheets and learning outcome assessment sheets. The data analysis techniques used are qualitative descriptive and quantitative descriptive. Based on the results of the research and discussion, data obtained on the increase in science learning outcomes on Movement and Style material for class VII G students at SMPN 13 Magelang after implementing learning using the demonstration learning model in cycle I was an average of 75 with 70% KKM completeness, after being carried out in cycle II on a regular basis. the average is 78 90% KKM completion. These results show that the Demonstration model can improve the learning outcomes of class VII G students at SMP Negeri 13 Magelang for the 2022/2023 academic year.